Financial Sustainability and Influence Dynamics in Yemen's Conflict-Affected NGO Landscape: Unveiling ‘Sheikh’ Organizations - Moosa Elayah (18134107) (2025)
This study examines the role of Sheikh NGOs as financial gatekeepers in Yemen’s NGO sector, showing how their control over aid distribution reinforces dependency and limits local NGOs' autonomy. Through interviews with 45 stakeholders, the research reveals the challenges that local NGOs face in achieving financial sustainability amid economic instability, political turmoil, and dwindling donor support. The findings indicate a significant asymmetry in funding, with Sheikh NGOs monopolizing resources, which constrains the flexibility and innovation of smaller NGOs. Integrating dependency theory, the study illustrates how reliance on intermediaries reinforces power imbalances, while collective impact theory highlights the potential for transformative partnerships. Successful collaborations, like those between the Youth Leadership Development Foundation and local NGOs, underscore the need for Sheikh NGOs to adopt more supportive roles, empowering smaller organizations. This study calls for a reconfiguration of roles within Yemen's NGO sector, advocating a shift from dependency to partnership. In fostering collaboration and supporting local NGO autonomy, stakeholders can build a more equitable and resilient framework, ultimately enhancing humanitarian efforts in Yemen. Other Information Published in: VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11266-024-00714-y